2021
DOI: 10.5935/jetia.v7i29.751
|View full text |Cite
|
Sign up to set email alerts
|

Determination of factors affecting the consumption behavior of ornamental plant consumers: Şanliurfa sampling of Turkey

Abstract: Ornamental plants are a sector that meets the spiritual and visual needs of people, improves the physical properties of the space they are used in, and contributes significantly to the economy and employment with the added value it creates. Şanlıurfa has an important potential for ornamental plants due to its geothermal resource and seasonal characteristics. The purpose of this study is to determine the factors that affect the consumption behavior of ornamental plant consumers in Şanlıurfa. The material of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…The association between an individual's marital status and consumer buying patterns has been sparsely studied. Several past studies found that food habits and buying behavior of people are promptly altered depending on their marital status (Aydogdu & Kaya, 2020;Sen et al 2021). However, few researchers have studied the effect of individual marital status on their tendency to indulge in compulsive buying.…”
Section: Marital Status and Compulsive Buyingmentioning
confidence: 99%
“…The association between an individual's marital status and consumer buying patterns has been sparsely studied. Several past studies found that food habits and buying behavior of people are promptly altered depending on their marital status (Aydogdu & Kaya, 2020;Sen et al 2021). However, few researchers have studied the effect of individual marital status on their tendency to indulge in compulsive buying.…”
Section: Marital Status and Compulsive Buyingmentioning
confidence: 99%
“…Sports consumption belongs to a higher level of demand, and only after meeting physiological, safety, and other needs will people consume sports to meet the needs of self-realization [16]. In essence, the upgrading of the sports consumption structure is mainly reflected in the transformation from physical consumption to participatory and ornamental consumption, and through the pursuit of high-quality sports products and services, driving the rise of high-end sports consumption brands [17][18][19][20][21][22][23]. From the perspective of macro, mesoscopic, and microscopic, the upgrading of sports consumption structure includes the optimization of the sports market structure, the adaptation of the supply structure and demand structure of the sports industry, and the improvement of the supply level of enterprise services and products [24].…”
Section: Introductionmentioning
confidence: 99%
“…Livestock enterprises are mostly composed of small and scattered family businesses and the production of feed crops in these enterprises is not adequate [13]. The increase in input prices, while causing a decrease in the production of fodder crops, this situation also hampers the development of animal production potential in Turkey at the desired level [14]. Another reason that makes the wheat production important in Turkey is that forage crops as the first or second product has the limited cultivation of agricultural land [15].…”
Section: Introductionmentioning
confidence: 99%